Structure of brewer's spent grain lignin and its interactions with gut microbiota in vitro - Ohra-aho, Taina; Niemi, Piritta; Aura, Anna-Maija; Orlandi, Marco; Poutanen, Kaisa; Buchert, Johanna; Tammminen, Tarja (American Chemical Society, 2016)
Lignin is part of dietary fiber, but its conversion in the gastrointestinal tract is not well understood. The aim of this work was to obtain structural information on brewer's spent grain (BSG) lignin and to understand the behavior of the polymeric part of lignin exposed to fecal microbiota. The original BSG and different lignin fractions were characterized by pyrolysis-GC/MS with and without methylation. Methylation pyrolysis proved that the ratio between guaiacyl and syringyl units was similar in all lignin samples, but the ratio between p-coumaric and ferulic acids varied by the isolation method. Combined pyrolysis results indicated higher acylation of gamma-OH groups in syringyl than in guaiacyl lignin units. The polymeric lignin structure in the alkali-soluble fraction after enzymatic hydrolysis was slightly altered in the in vitro colon fermentation, whereas lignin in the insoluble residue after enzymatic treatments remained intact.
Keywords: brewer's spent grain; lignin; Py-GC/MS; TMAH/Py; in vitro fermentation; colon microbiota; tetramethylammoniumhydroxide TMAH; ferulic acid; analytical pyrolysis; gas ghromatography; phenolic compounds; electron impact; dietary fiber; mass spectra; products